PENGARUH VARIABEL MAKRO EKONOMI TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA PERIODE 2009 - 2014 - sodiq, Amirus (Universitas Islam Negeri Sunan Kudus, 2015)
This research aims to explain the influence analysis of Inflation, GrossDomestic Bruto, and Interest Rate to the Return on Asset (ROA) of IslamicBanking period 2009-2014. The sampling technique used is purposivesampling. This research sample gained from three Islamic banks and the datawere obtained from published financial statement of Bank of Indonesia. Dataanalysis technique used multiple linier regression analysis. Where previouslydata had been tested with the classical assumption include data normality test,heteroscedasticity, multicollinearity and autocorrelation. F Test result showedthat simultaneous variable of Inflation, Gross Domestic Bruto, and InterestRate have a significant effect on ROA while T Test result showed that partiallyInflation haven’t a significant effect on ROA while GDP have a positive andsignificant effect on ROA while Interest Rate have a significant effect on ROA.